Does HIV status affect the aetiology, bacterial resistance patterns and recommended empiric antibiotic treatment in adult patients with bloodstream infection in Cambodia?. Issue 4 (7th January 2013) - Phe, Thong; Vlieghe, Erika; Reid, Tony; Harries, Anthony D.; Lim, Kruy; Thai, Sopheak; De, Birgit; Veng, Chhunheng; Kham, Chun; Ieng, Sovann; van, Johan; Jacobs, Jan
Abstract Objective The microbiologic causes of bloodstream infections (BSI) may differ between HIV‐positive and HIV‐negative patients and direct initial empiric antibiotic treatment (i.e. treatment before culture results are available). We retrospectively assessed community‐acquired BSI episodes in adults in Cambodia according to HIV status for spectrum of bacterial pathogens, antibiotic resistance patterns and appropriateness of empiric antibiotics. Methods Blood cultures were systematically performed in patients suspected of BSI in a referral hospital in Phnom Penh, Cambodia. Data were collected between 1 January 2009 and 31 December 2011. Results A total of 452 culture‐confirmed episodes of BSI were recorded in 435 patients, of whom 17.9% and 82.1% were HIV‐positive and HIV‐negative, respectively. Escherichia coli accounted for one‐third (n = 155, 32.9%) of 471 organisms, with similar rates in both patient groups. Staphylococcus aureus and Salmonella cholereasuis were more frequent in HIV‐positive vs. HIV‐negative patients (17/88 vs. 38/383 (P = 0.02) and 10/88 vs. 5/383 (P < 0.001)). Burkholderia pseudomallei was more common in HIV‐negative than in HIV‐positive patients (39/383 vs. 2/88, P < 0.001). High resistance rates among commonly used antibiotics were observed, including 46.6% ceftriaxone resistance among E. coli isolates. Empiric antibiotic treatments were similarly appropriate in both patient groups but did not cover antibiotic‐resistant E. coli (both patient groups), S. aureus (both groups) and B. pseudomallei (HIV‐negative patients). Conclusion The present data do not warrant different empiric antibiotic regimens for HIV‐positive vs. HIV‐negative patients in Cambodia. The overall resistance rates compromise the appropriateness of the current treatment guidelines.